2005
DOI: 10.1007/s00018-005-5370-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin

Abstract: Lactoferrin is an iron-binding glycoprotein of the transferrin family. Abundant expression and secretion of lactoferrin, in particular in milk and fluids of the digestive tract, are related to its implication in the first line of host defense. Lactoferrin is also a prominent component of the secondary granules of neutrophils (PMNs) and is released in infected tissues and blood during the inflammatory process. In addition to its direct antimicrobial properties, the abilities of lactoferrin to regulate the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
13

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(139 citation statements)
references
References 107 publications
2
117
0
13
Order By: Relevance
“…Corpora amylacea are protein aggregates of lactoferrin (Sfanos et al 2009), delivered by neutrophils following acute prostate inflammation (Legrand et al 2005, Sfanos et al 2009). As expected (De Marzo et al 2007, Sfanos et al 2009, Yanamandra et al 2009), we have observed corpora amylacea adjacent to infiltrating inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Corpora amylacea are protein aggregates of lactoferrin (Sfanos et al 2009), delivered by neutrophils following acute prostate inflammation (Legrand et al 2005, Sfanos et al 2009). As expected (De Marzo et al 2007, Sfanos et al 2009, Yanamandra et al 2009), we have observed corpora amylacea adjacent to infiltrating inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lactoferrin (Lf), an iron-binding protein present at mucosal sites and in many bodily fluids, was shown to facilitate binding of Ad5 to human epithelial cells and enhance infection via a CAR-independent manner using a yet undefined receptor (Johansson et al, 2007). Interestingly, Lf is mainly known for its immunomodulatory properties, which enhance anti-microbial and anti-inflammatory responses (Legrand et al, 2005). High levels of Lf present during inflammation were recently shown to directly recruit and activate DCs (de la Rosa et al, 2008;Spadaro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…В частности, α2-МГ является ингибитором протеиназ, высво-бождающихся при воспалении, транспортером гор-монов и цитокинов, участвует в распознавании и презентации инфекционных антигенов, регуляции пролиферации и апоптоза, ремоделировании тка-ней [4]. ЛФ также обладает выраженными антибак-териальными и противовирусными свойствами, ре-гулирует синтез цитокинов, является высокочув-ствительным маркером воспаления [5]. Избыток цитокинов (особенно ИЛ-6 для α2-МГ и хемокина ИЛ-8 для ЛФ) активирует синтез этих белков.…”
Section: проблемы эндокринологии 6 2014unclassified
“…Можно предположить, что чем выше содержание α2-МГ при АИТ и ДТЗ и чем мед-леннее их нормализация при лечении, тем выше ве-роятность рецидивирования процессов. Аналогич-ная ситуация с ЛФ: направленность его воздействия на синтез цитокинов регулируется балансом свобод-ных и связанных с железом форм ЛФ [5]. Поскольку при аутоиммунной патологии щитовидной железы наблюдается дефицит железа [9], избыток ЛФ в кро-ви не способствует улучшению ситуации, а напро-тив, поддерживает развитие воспалительных и ауто-иммунных процессов.…”
Section: проблемы эндокринологии 6 2014unclassified
See 1 more Smart Citation